A positive feedback loop of the TAZ/β-catenin axis promotes Helicobacter pylori-associated gastric carcinogenesis - Xu, Xinbo; Shu, Chunxi; Wu, Xidong; Ouyang, Yaobin; Cheng, Hong; Zhou, Yanan; Wang, Huan; He, Cong; Xie, Chuan; He, Xingxing; Hong, Junbo; Lu, Nonghua; et al. (Frontiers in Microbiology, 2022)
Background Helicobacter pylori infection is the strongest known risk factor for gastric cancer. The Hippo signaling pathway controls organ size and maintains tissue homeostasis by coordinately regulating cell growth and proliferation. Here, we demonstrate the interactive role of TAZ, the transcriptional coactivator of the Hippo pathway, and beta-catenin in promoting the pathogenesis of H. pylori infection. Methods TAZ expression was evaluated in human gastric tissues and H. pylori-infected insulin–gastrin (INS-GAS) mice. Western blot, immunofluorescence, immunohistochemistry, and RT–PCR assays were performed. Coimmunoprecipitation was performed to examine the interaction between TAZ and β-catenin. TAZ and β-catenin were silenced using small interfering RNAs. HA-β-catenin and Flag-TAZ were constructed. Results Increased TAZ was noted in human gastric cancer tissues compared to chronic gastritis tissues and in H. pylori-positive gastritis tissues compared to H. pylori-negative gastritis tissues. In addition, H. pylori infection induced TAZ expression and nuclear accumulation in the gastric tissue of INS-GAS mice and cultured gastric epithelial cells, which was dependent on the virulence factor CagA. Moreover, TAZ or β-catenin knockdown significantly suppressed H. pylori infection-induced cell growth, survival, and invasion. Furthermore, the interactive regulation of TAZ and β-catenin activation was revealed. Finally, β-catenin was required for H. pylori-induced TAZ activation. Conclusion These findings suggest the existence of a positive feedback loop of activation between TAZ and β-catenin that could play an important role in CagA+ H. pylori infection-induced gastric carcinogenesis. TAZ inhibition represents a potential target for the prevention of H. pylori infection-associated gastric cancer.